Peran Guru sebagai Demonstrator dalam Pembelajaran Menulis Aksara Jawa - Anisa Rizqi Aulya; Joko Daryanto; Siti Istiyati (Universitas Sebelas Maret, 2026)
This study aims to describe the teacher's role as a demonstrator in Javanese script writing instruction at SD Negeri Ngrandu. Javanese script is one of the local cultural heritages that needs to be preserved through elementary education; however, many students still experience difficulties in writing Javanese script correctly. This study employed a qualitative approach with a descriptive method. The research was conducted at SD Negeri Ngrandu, Boyolali Regency, involving one third-grade teacher and twelve third-grade students as research subjects. Data were collected through observation, interviews, tests, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, consisting of data collection, data condensation, data display, and conclusion drawing. The findings revealed that the teacher had performed the role of demonstrator through several indicators, including mastery of the material, material demonstration, technical and procedural accuracy, the use of varied techniques and media, as well as guidance and feedback. The teacher demonstrated the writing of nglêgêna Javanese script directly, involved students in writing practices, explained writing procedures, utilized learning media such as whiteboards, worksheets, and script cards, and provided guidance and corrections on students’ work. However, the implementation was not yet optimal due to limited learning media, insufficiently detailed explanations, and uneven feedback provided to students. Therefore, the teacher’s role as a demonstrator has been implemented well but still requires improvement to enhance the effectiveness of Javanese script writing instruction.